In situ X-ray spectroscopies beyond conventional X-ray absorption spectroscopy on deciphering dynamic configuration of electrocatalysts - Jiali Wang; Chia-Shuo Hsu; Tai-Sing Wu; Ting-Shan Chan; Nian-Tzu Suen; Jyh-Fu Lee; Hao Ming Chen (Nature Communications, 2023)
Abstract Realizing viable electrocatalytic processes for energy conversion/storage strongly relies on an atomic-level understanding of dynamic configurations on catalyst-electrolyte interface. X-ray absorption spectroscopy (XAS) has become an indispensable tool to in situ investigate dynamic natures of electrocatalysts but still suffers from limited energy resolution, leading to significant electronic transitions poorly resolved. Herein, we highlight advanced X-ray spectroscopies beyond conventional XAS, with emphasis on their unprecedented capabilities of deciphering key configurations of electrocatalysts. The profound complementarities of X-ray spectroscopies from various aspects are established in a probing energy-dependent “in situ spectroscopy map” for comprehensively understanding the solid-liquid interface. This perspective establishes an indispensable in situ research model for future studies and offers exciting research prospects for scientists and spectroscopists.